Different homicidal mechanical asphyxial death and disposal of dead body to conceal crime: A case series - Vinod Kumar,; Tarun Dagar,; Jai Prakash Soni,; Chander Bhan, (Asian Journal of Medical Sciences, 2025)
Homicide is the killing of a human being be another human being. Various methods are adopted by a person to kill other person (such as by various weapons and other mechanical methods etc.) such as using blunt and sharp weapons, mechanical methods, and firearm ammunition. Among the mechanical methods; strangulation by ligature, throttling, and smothering are used commonly however gagging, mugging, etc., are also used which are classified under mechanical asphyxial death. In many of the cases, more than one mechanical method is adopted by the assailant to kill the person such as throttling and smothering, strangulation by ligature and gagging. In many of the cases, the body of the deceased is disposed of by the accused by throwing it in an area away from original occurrence of place of crime or dumps it in any water body, etc., to conceal the crime.